2018
DOI: 10.1038/s41591-018-0206-4
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenetic contributions to amyloid beta and tau spreading in the human cortex

Abstract: Tau and beta-amyloid (Aβ) proteins accumulate along neuronal circuits in Alzheimer’s disease (AD). Unraveling the genetic background for the regional vulnerability of these proteinopathies can help in understanding the mechanisms of pathology progression. To that end, we developed a novel graph theory approach and used it to investigate the intersection of longitudinal Aβ and tau PET imaging of healthy adult individuals and the genetic transcriptome of the Allen Human Brain Atlas. We identified distinctive pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
130
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(151 citation statements)
references
References 70 publications
15
130
0
Order By: Relevance
“…Together, it is thus possible that functional connectivity of fast tau accumulating regions may facilitate the spread of tau to their closely connected neighbors. An alternative explanation is, that network-forming regions show similar susceptibility for developing tau pathology: Specifically, previous studies have shown that similar gene expression is found among functionally connected regions 31,32 , where similar gene expression across brain regions is associated with shared susceptibility to develop AD pathology, including amyloid, tau and neurodegeneration [33][34][35] . Thus, it is possible that the association between functional connectivity and tau accumulation rates is in part determined by shared genetic susceptibility for developing tau pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Together, it is thus possible that functional connectivity of fast tau accumulating regions may facilitate the spread of tau to their closely connected neighbors. An alternative explanation is, that network-forming regions show similar susceptibility for developing tau pathology: Specifically, previous studies have shown that similar gene expression is found among functionally connected regions 31,32 , where similar gene expression across brain regions is associated with shared susceptibility to develop AD pathology, including amyloid, tau and neurodegeneration [33][34][35] . Thus, it is possible that the association between functional connectivity and tau accumulation rates is in part determined by shared genetic susceptibility for developing tau pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Spatial gene expression patterns in the human brain have been studied to unravel the pathogenic mechanisms underlying amyloid-β and tau pathology progression in Alzheimer’s disease, revealing proteins that co-aggregate with amyloid-β and tau, and protein homeostasis components 13,14 . Interestingly, by integrating Allen Human Brain Atlas (AHBA) gene expression data 15 with magnetic resonance imaging of PD patients, the regional expression pattern of MAPT and SNCA was associated with loss of functional connectivity in PD 16 , and regional expression of synaptic transfer genes was related to regional gray matter atrophy in PD 17 .…”
Section: Introductionmentioning
confidence: 99%
“…The asymmetrical progression of Alzheimer's disease neuropathology in different brain regions may reflect selective neuronal vulnerabilities local to each region (Mattson and Magnus, 2006;Saxena and Caroni, 2011;Wu et al, 2014;Schmitz and Nathan Spreng, 2016). However, evidence in both mouse models of Alzheimer's disease (De Calignon et al, 2012;Liu et al, 2012) and in human Alzheimer's disease patients (Schmitz et al, 2018;Sepulcre et al, 2018) indicates that neuropathology also spreads across anatomically and functionally connected brain regions. It is therefore possible that pathologies arising from selective neuronal vulnerability local to a given brain region might precede and predispose the subsequent spread of pathology across networks (Warren et al, 2013).…”
Section: Introductionmentioning
confidence: 99%